KEHIDUPAN PENYINTAS PASCABENCANA BANJIR BANDANG DI DESA KOTA LINTANG BAWAH DALAM FOTOGRAFI DOKUMENTER - Dimas Rizkar; Benny Kurniadi (STKIP Subang, 2026)
Indonesia is highly prone to hydrometeorological disasters, and the flash flood that struck Kota Lintang Bawah village, Aceh Tamiang, in late 2025 left nearly eighty percent of homes destroyed. While mass media coverage largely focused on the dramatic moment of the disaster itself, this creative work examines a phase that receives far less visual attention: the long process of adaptation afterward. Using a late photography approach, the author revisited the location weeks after the flood to document how survivors rebuilt their social and economic lives amid the ruins. The creation process consisted of field observation, interviews with the village head, and literary study, followed by documentary photo-story production using the EDFAT technique and minimal post-processing to preserve visual authenticity. Of 135 photographs taken, 37 works (23 single photographs and 14 photo series) were selected and arranged into a narrative moving from the scale of environmental damage, daily survival activities, and volunteer assistance, to trauma-healing sessions. The resulting photo story shows that the contrast between physical devastation and the residents' resilience, sociability, and hope forms the central visual and emotional message of the work, positioning documentary photography as both a historical record and a medium for public empathy toward post-disaster recovery.